What hinders the use of ICT among academic staff at Yemen’s public universities? - Yahya M Aldheleai; Roselan Baki; Zaidatun Tasir; Waleed Alrahmi (Center for Humanities and Innovation Studies, 2019)
The purpose of this study was to investigate the use of Information Communication Technology (ICT) in Yemen public universities. Three academic staff from Hodeida, Amran and Thamar universities were the participants of this study. The qualitative method was employed with one-to-one interview as an instrument of the data collection. Thematic analysis was employed to identify the patterns that reflect the factors affecting ICT use in universities. The findings revealed that the use of ICTs in Yemen’s universities still depends on lecturers' self-initiative. The lecturer who has skills of using ICT appeared to have a positive attitude towards the use of ICT in their teaching. There is no type of social influence on lecturer’s use of ICT in their teaching. The poor infrastructure, poor facilitating condition and lack of the technical support stand as significant ICT barriers integration in Yemen’s Universities. All forms of online communication are absent in all three universities. The participants of this study urged their universities top management to provide proper facilitating conditions and training programs to enable their academic staff to cope up to 21st-century teaching and technologies.